High-density haplotype structure and association testing of the insulin-degrading enzyme (IDE) gene with type 2 diabetes in 4,206 people. - Florez, J; Wiltshire, S; Agapakis, C; Burtt, N; de Bakker, P; Almgren, P; Bengtsson Boström, K; Tuomi, T; Gaudet, D; Daly, M; Hirschhorn, J; McCarthy, M; et al. (2006)
The insulin-degrading enzyme is responsible for the intracellular proteolysis of insulin. Its gene IDE is located on chromosome 10, in an area with suggestive linkage to type 2 diabetes and related phenotypes. Due to the impact of genetic variants of this gene in rodents and the function of its protein product, it has been proposed as a candidate gene for type 2 diabetes. Various groups have explored the role of the common genetic variation of IDE on insulin resistance and reported associations of various single nucleotide polymorphisms (SNPs) and haplotypes on both type 2 diabetes and glycemic traits. We sought to characterize the haplotype structure of IDE in detail and replicate the association of common variants with type 2 diabetes, fasting insulin, fasting glucose, and insulin resistance. We assessed linkage disequilibrium, selected single-marker and multimarker tags, and genotyped these markers in several case-control and family-based samples totalling 4,206 Caucasian individuals. We observed no statistically significant evidence of association between single-marker or multimarker tests in IDE and type 2 diabetes. Nominally significant differences in quantitative traits are consistent with statistical noise. We conclude that common genetic variation at IDE is unlikely to confer clinically significant risk of type 2 diabetes in Caucasians.